Job Satisfaction and Job Performance in PT XYZ - Valianawaty, Cindy; Sutanto, Eddy Madiono (TRIKONOMIKA, 2015)
This study was aimed to describe the measurements levels of job satisfaction and job performance, as well as to examine the positive effects on job satisfaction of employees performance in PT XYZ. This study used a quantitative approach, primary data which was obtained from the questionnaires to 60 employees, and secondary data from the company record, literature and previous research. The conclusion was, first, that each of individual employees had different job satisfaction. Second, the job performance was individual. Third, job satisfaction was high, working condition indicator as the highest and social service indicator as the lowest. Fourth, job performance was high, quality of work indicator as the highest, as well as cooperative and dependability indicator as the lowest. Fifth, the job satisfaction had no positive effect on job performance in PT XYZ.